CO2-enhanced hydrogen permeability of dual-layered A-site deficient Ba0.95Ce0.85Tb0.05Zr0.1O3-d-based hollow fiber membrane - Shang, Y.; Wei, L.; Meng, X.; Meng, B.; Yang, N.; Sunarso, J.; Liu, Shaomin (Elsevier BV, 2018)
© 2017 Elsevier B.V. Hydrogen (H 2 )-selective proton conducting perovskite membrane is the low cost alternative of palladium membrane. In this work, we report the preparation of an A-site deficient Zr-doped proton conductor composition of Ba 0.95 Ce 0.85 Tb 0.05 Zr 0.1 O 3-d (BCTZ) in the dual-layer hollow fiber configuration consisting of Ni-BCTZ inner porous layer and BCTZ outer dense layer, denoted as BCTZ/Ni-BCTZ hollow fiber via co-spinning, co-sintering, and reduction (in hydrogen) processes. The presence of Zr 4+ in BCTZ perovskite lattice leads to higher CO 2 resistance for BCTZ relative to Ba 0.95 Ce 0.95 Tb 0.05 O 3-d (BCT) as revealed by their CO 2 -temperature programmed desorption results. H 2 permeation flux of dual-layer BCTZ/Ni-BCTZ hollow fiber reaches a maximum of 0.41 mL min -1 cm -2 at 900 °C. When CO 2 was introduced in the permeate side, H 2 permeation flux was enhanced with respect to the CO 2 -absent case, which is attributed to the presence of reverse water-gas shift reaction that consumes the permeated H 2 to produce carbon monoxide and water. The dual-layer BCTZ/Ni-BCTZ hollow fiber showed stable H 2 permeation fluxes when operated at 800 °C in CO 2 -containing permeate atmosphere for 25 days. Its original morphology and structure were retained following this long term operational test; highlighting its potential use for H 2 separation in CO 2 -containing reactions and processes.